Analisis Hubungan Keberanian Mengambil Risiko dan Norma Subjektif terhadap Intensi Berwirausaha Mahasiswa: Temuan yang Tidak Signifikan - Sryna, Maria Grace; Nainggolan, Eben Ezer; Muslikah, Etik Darul (Innovative: Journal Of Social Science Research, 2025)
Indonesia has a population of 284 million in 2024, with 69.3% being of productive age. However, the entrepreneurship ratio is only 3.47%, much lower than developed countries, while the unemployment rate reaches 4.82%. This study aims to analyze the relationship of risk-taking courage and subjective norms to entrepreneurial intention in college students. The research method used a correlational quantitative design with a Likert scale-based questionnaire instrument, involving a sample of 17 August Surabaya University students selected by accidental sampling. The results of the analysis showed that risk-taking courage (p = 0.533) and subjective norms (p = 0.129) did not have a significant relationship to entrepreneurial intention, either individually or simultaneously (Chi-Square = 2.177; p = 0.337). Other factors, such as self-efficacy and intrinsic motivation, may be more dominant in influencing entrepreneurial intention. In conclusion, although risk-taking courage and subjective norms are important, they are not enough to explain students' entrepreneurial intention thoroughly.